An inequality for a quadratic functional - Chau, Le Khanh (Vietnam Journal of Mechanics, 2009)
An inequality is proved for a quadratic functional with the logarithmic kernel. The best constant of this inequality and the corresponding function for which the equality holds are found precisely.